If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-2)(x-7)=9
We move all terms to the left:
(x-2)(x-7)-(9)=0
We multiply parentheses ..
(+x^2-7x-2x+14)-9=0
We get rid of parentheses
x^2-7x-2x+14-9=0
We add all the numbers together, and all the variables
x^2-9x+5=0
a = 1; b = -9; c = +5;
Δ = b2-4ac
Δ = -92-4·1·5
Δ = 61
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-9)-\sqrt{61}}{2*1}=\frac{9-\sqrt{61}}{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-9)+\sqrt{61}}{2*1}=\frac{9+\sqrt{61}}{2} $
| -5=4+x/3 | | 7-3x=5x-2(4x+1) | | 5-3y=65 | | -15=18x-4 | | -2=t3-11 | | (2x/5)-(x-3)=3 | | -7=2+s | | 5(-1+5x)+5(-8x-2)=-4x-8x | | -10+4x=74 | | (2x+9/3)+(2/3)=-(3x/2) | | (2x+9)/3+(2/3)=-(3x/2) | | 6a=-5a+6a | | 2.75j+2.25-1.5j+3=0 | | 23x+5x=3 | | 4x^-10x-24=0 | | 4y^2-5y+8=0 | | 0.2(2x+1)=0.04(2x-3) | | 2(3h-17)=2(3h-7) | | 8y^2-7y-1=0 | | 5-0.5x=2x-5 | | 2(400-x)+2x=800 | | 12-h=18 | | 7x+2+10x+3=180 | | 12-2n=14 | | -4x+85=65 | | 9x+5x/2=115 | | x+2/4+x-3/3=1 | | 9-3x=4+2x | | 10x+21(x-4)=71 | | 4x+2=-5x+4 | | -8-2x=44 | | 11x+9=22x-12 |